Women's Economic Capacity and Children's Human Capital Accumulation - Jacobus de Hoop; Patrick Premand; Furio C. Rosati; Renos Vakis (Institute of Labor Economics (IZA), 2017)
Programs that increase the economic capacity of poor women can have cascading effects on children's participation in school and work that are theoretically undetermined. We present a simple model to describe the possible channels through which these programs may affect children's activities. Based on a cluster-randomized trial, we examine how a program providing capital and training to women in poor rural communities in Nicaragua affected children. Children in beneficiary households are more likely to attend school one year after the end of the intervention. An increase in women's influence on household decisions appears to contribute to the program's beneficial effect on school attendance.
Keywords: D13; H43; I25; J22; J24; O15; O22; Q12; 330; women's economic capacity; female empowerment; Nicaragua; child labor; human capital accumulation; field experiment